Quantifying Stress Responses in Buried Gas Pipelines under Heavy-Duty Vehicle Loads - L’ubomir Gajdos; Martin Sperl; Jan Kec (Scientific Research, New Technologies and Applications Vol. 7, 2024)
The aim of this article is to quantify the loads exerted by heavy-duty vehicles when crossing over a buried pipeline. These loads are important in deciding about the use of protective sleeves (casings) applied to gas pipelines in regions with increased demands on pipeline operation safety. Experiments were conducted on a test pipe section made from L360NE pipeline steel equipped with strain gauges along the pipe perimeter to measure strains in the axial and circumferential directions. Strain measurements were taken after back-filling the pipe trench, then during vehicle crossings over the empty pipe, and again after pressurizing the test pipe with air. Besides this, an engineering estimation of the state of stress of a buried pipe was also made. The results showed that the weight of the backfill, acting on an empty pipe, causes an ovalness of the circular cross-section of the pipe giving thus the rise of through-wall bending stresses with the tensile stress at the outside surface at the 3 and 9 o´clock positions, and compressive stress at the inside surface. At the 6 and 12 o´clock positions, the stresses are tensile at the inside surface and compressive at the outside surface. Strain-based hoop stresses at the surface of the empty test pipe were found to exceed 30 MPa after back-filling the trench and increased to more than 40 MPa during the vehicle crossings. Axial stresses reached extremes of around 17 MPa in compression and 12 MPa in tension.